Interaction Between Teacher and Students in Virtual Classroom - Adhikari, Khadak Raj (Academic Journal of Mathematics Education, 2021)
Several school and colleges of Nepal have adopted online and virtual teaching instead of physical class during the pandemic situation of covid-19. The main objective of this action research is to find the interaction between teachers and students in virtual classroom. 161 students have been taken as sample from different grades 5,8,9 and 12 from the school of Gandaki Province. During the virtual class, students neither responded the teacher nor involved in the classroom interaction. After the regular treatment for couple of months, in comparison to the initial phase the remarkable improvements were seen in the student’s participation, attendance, assignments and classroom interactions in the virtual classroom.